Every breath - Sparks, Nicholas; Michael, Sean Cameron, 1969-; Johansson, Vanessa, 1980- (New York, NY : Hachette Audio, 2018)
A chance encounter becomes a transcendent turning point for two very different people--the conflicted daughter of an ALS patient and a Sunset Beach newcomer from Zimbabwe who aims to meet his birth father.
Read by Sean Cameron Michael and Vanessa Johansson.
Keywords: Amyotrophic lateral sclerosis -- Patients -- Fiction; Audiobooks; Romance fiction